Optimal indirect estimation for linear inverse problems with discretely sampled functional data. (25th October 2021) - Pricop-Jeckstadt, Mihaela
Abstract: Optimal mean estimation from noisy independent pathes of a stochastic process that are indirectly observed is an issue of great interest in functional inverse problems. In this paper, minimax rates of convergence for a class of linear inverse problems with correlated noise, general source conditions and various degrees of ill-posedness are proven in a continuous setting, when the pathes are entirely observed, and in a projected framework. The phase transition phenomenon characteristic to the functional data analysis appears also here and the thresholds that separate the sparse and the dense data set scenarios are computed for different smoothness conditions. The common design proves to be a special case of the independent design in view of the interpretation of the sampling properties via s -numbers and the price to pay for the data correlation turns out to be high. Finally. numerical experiments involving Abel's integral operator illustrate the goodness-of-fit of the Tikhonov estimator in various scenarios reflecting the common and independent design as well as sparse and dense sampling.